Methods of Household Consumption Measurement Through Surveys : Experimental Results from Tanzania - Beegle, Kathleen; De Weerdt, Joachim; Friedman, Jed; Gibson, John (2012)
Consumption expenditure has long been the preferred measure of household living standards. However, accurate measurement is a challenge and household expenditure surveys vary widely across many dimensions, including the level of reporting, the length of the reference period, and the degree of commodity detail. These variations occur both across countries and also over time within countries. There is little current understanding of the implications of such changes for spatially and temporally consistent measurement of household consumption and poverty. A field experiment in Tanzania tests eight alternative methods to measure household consumption on a sample of 4,000 households. There are significant differences between consumption reported by the benchmark personal diary and other diary and recall formats. Under-reporting is particularly relevant in illiterate households and for urban respondents completing household diaries; recall modules measure lower consumption than a personal diary, with larger gaps among poorer households and households with more adult members. Variations in reporting accuracy by household characteristics are also discussed and differences in measured poverty as a result of survey design are explored. The study concludes with recommendations for methods of survey based consumption measurement in low-income countries.